Analysis of The Progress and Setback of Islamic Civilization of The Mughal, Safawi and Ottoman Türkiye - Malik, Adam (TAJDID, 2023)
The purpose of this article is to find out the progress and decline experienced by the three major empires during the Islamic civilization, namely the Mughal Empire, the Safavid Empire and the Ottoman Empire. The analysis was carried out to describe the various advances experienced by the three kingdoms along with the factors that led to their decline. The research method used is Library Research. The results of the study show that the progress of Islamic civilization during the Mughal Empire was one of them influenced by Sulakhul politics which gave a new breath to Indian society at that time. Meanwhile, one of the factors that caused the collapse of the Mughal empire was an attack from the British army. The progress of the Safavid kingdom tended to be in the field of science, ranging from religious knowledge to general knowledge. Among the reasons for its decline were the endless attacks from the Ottoman Turks and the Afghans. The Ottoman Empire was one of the largest occupations that made a significant contribution to Islamic civilization. One of them is the conquest of Constantinople as promised by the Prophet. The decline of the Turkish empire was caused by several factors both internal and external, ranging from incompetent successors to western attacks.